Apatinib in gastric carcinoma: A case report of partial response for first‐line treatment in advanced disease. Issue 5 (28th December 2016) - Wang, Yaping; Bi, Minghong; Zhang, Haoran; Gao, Zhenyuan; Zhou, Hairong; Chang, Shu
Abstract: Gastric cancer (GC) is the most common gastrointestinal malignant tumor, with a gradual increasing incidence throughout the world. Mostly GC is diagnosed in its late stage. To date, there is no usable standardized treatment regimen for patients with advanced GC. Apatinib mesylate, small‐molecule vascular endothelial growth factor receptor‐2 (VEGFR‐2) tyrosine kinase inhibitor (TKI), has been approved as third‐line treatment for patients with advanced gastric adenocarcinoma in China, October, 2014. Till now, there is no case report about apatinib as first‐line treatment for patients with advanced GC in literature. We present an 83‐year‐old Chinese man with advanced gastric adenocarcinoma, who received apatinib as first‐line option and obtained clinical benefit within 2 weeks. The lung metastases disappeared completely and the liver metastases shrank significantly. The patient's progression‐free survival was 163 days and overall survival was 201 days. This paper reviews and discusses apatinib as a new targeted drug for patients with advanced GC by comparison with other effective molecular‐targeted therapy.